A rare presentation of spinal schwannoma causing conus medullaris syndrome: a case series on surgical outcome - Mor Japar Khan, Ed Simor Khan; Ang Poh Thean, Charles; Zakaria@Mohamad, Zamzuri; Awang, Mohamed Saufi; Karupiah, Rajandra Kumar; Awang, Mohd Shukrimi (Indian Orthopaedic Research Group, 2020)
Introduction: Spinal schwannoma can occur anywhere along the spinal cord but is predominantly seen in the cervical and thoracic region.It composes mainly of well-differentiated schwann cell and is benign in nature. It is typically seen in the peripheral nerves and is commonly associated with neurofibromatosis. Up to 80% of cases, spinal schwannoma is reported to be intradural in location and 15% of cases have both intradural and extradural components. Spinal schwannoma rarely causes conus medullaris syndrome. Case Report: In this case series, all three female patients in their 4th and 5th decades of life presented with conus medullaris syndrome. Lower back pain, radiculopathy, lower limb weakness, and urinary incontinence are their main clinical presentation. Magnetic resonance imaging shows a well-defined intradural, extramedullary mass compressing onto the conus medullary region. These patients undergone microscopic assisted excision of the tumor and had remarkably good early outcome despite the advanced presentation of neurological deficit. Conclusion: Despite the late presentation with significant neurological deficit, surgical excision of spinal schwannomas carries a good prognosis postoperatively due to their benign nature and extramedullary location.